Regional Problems and Policies in Latin America - Cuadrado-Roura, Juan R.; Aroca, Patricio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This contributed volume is the first book in English to offer a current and critical vision of regional problems and policies in the countries of Latin America. The book is in three main parts: a general overview of regional processes and trends in Latin America as a whole; country-level coverage of seven individual countries; and comparative analyses of common major problems such as migration, education, labor, poverty, decentralization, exports and foreign direct investments. Written by renowned academics and experts from the region, the book seeks to provide a better understanding of regional challenges and trends, regional disparities that exist in many Latin American countries and the increasing importance of metropolitan areas.
Part I: General Overview, Problems, Trends and Regional Policies in Latin America -- Part II: Analysis by Countries -- Part III: Horizontal and Comparative Analysis.
Keywords: Economics; Geography; Development Economics; Regional economics; Economics/Management Science; Regional/Spatial Science; Development Economics; Economic Geography